One Hundred Years of Solitude: rediscovery of Catasticta lycurgus (Godman & Salvin, 1880), a yellow butterfly from the Sierra Nevada de Santa Marta, Colombia (Lepidoptera: Pieridae) - Huertas, Blanca; Prieto, Carlos; Montero, Fredy; Adams, Mike; Le Crom, Jean François; Bollino, Maurizio; Correa-Carmona, Yenny; Padrón, Pablo Sebastián (Zootaxa, 2021)
Catasticta lycurgus is a striking endemic butterfly, restricted to high elevation habitats in the Sierra Nevada de Santa Marta, an isolated mountain range separate from the Andes in the north of Colombia. The type, which for almost a hundred years was the only known specimen, was collected in 1878 by Frederick Simons in the vicinity of Atánquez and was sent to the UK to be described by renowned naturalists Godman and Salvin in 1880. In 1972, explorers Adams and Bernard collected a second specimen of C. lycurgus in the locality of San Pedro at 2,900m of elevation in the Sierra Nevada de Santa Marta. These two specimens were the only known ones for many decades until recently, when Colombian entomologists found the species again in San Pedro de la Sierra and later, when a female was discovered in 2013. Here, we report the rediscovery of this rare and charismatic species, with new specimens collected near the type locality, which have not been reported previously. The female of C. lycurgus is described and illustrated for the first time as well the male genitalia of this species. We combine all information available to provide some insights on the systematic relationships of this species within the genus Catasticta Butler, discuss its distribution and provide a preliminary conservation assessment. Despite the newly collected specimens, the species remains very rare in the field and in collections.